Legal Convergence: Bridging Classical Fiqh School with Contemporary Legal Theory - Faidah, Nur; Juwantri, Feni (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
In the era of rapid globalization and modernization, Islamic law faces the challenge of remaining relevant and responsive to current developments. The classical school of jurisprudence, which has served as the foundation of Islamic law for centuries, must now confront complex contemporary issues. Contemporary legal theory offers a new approach that has the potential to integrate Islamic law with modern dynamics. This research examines the convergence between classical schools of jurisprudence and contemporary legal theory, underscoring the pressing need to integrate these two legal traditions. Utilizing an interdisciplinary approach, this research examines the primary characteristics, challenges, and opportunities associated with the legal integration process. This study also examines the adaptability of classical schools of jurisprudence in incorporating modern legal concepts. It is hoped that the research results will provide a conceptual and practical framework for legal convergence, which can be applied in Islamic law reform in various contexts. This convergence is crucial in addressing contemporary legal issues, including bioethics, cyber law, global financial regulation, and environmental challenges, thereby paving the way for productive dialogue between Islamic legal traditions and modern legal systems.